Knowledge and extractivism of Stryphnodendron rotundifolium Mart. in a local community of the Brazilian Savanna, Northeastern Brazil - Feitosa, Ivanilda Soares (J Ethnobiol Ethnomed, 2014)
BACKGROUND: This study aims to understand how the stem bark of Stryphnodendron rotundifolium Mart. is used by a rural community in the savanna of Northeastern Brazil, associated with a preliminary assessment involving plant population structure and extractivism in the main sites of collection. METHODS: A population structure study and analysis of bark extractivism was conducted in two sites: one within the forest and another at its edge. We had the intention of testing whether there are differences between these sites; since the local extractive practice is prohibited, expecting more intense extraction in the forest interior than its edge by the local fiscalization. We interviewed 120 informants who reported knowing and using the species, and also the places of extractivism. We also calculated quantitative measures of local knowledge, and the influence of gender and age on the knowledge about this species. RESULTS: Knowledge of the uses was evenly distributed between men and women. A total of 28 specimens were recorded at Site 1, whereas 23 were identified at Site 2, with the specimens at both sites distributed in 4-diameter classes with 4-cm intervals. Nine of the specimens found in Site 1 (32.14%) showed some sign of extraction. No specimen from Site 2 showed signs of extraction. In Site 1, the total area of stem bark removed was 43,468 cm(2), and the total area of stem bark available was 33,200 cm(2). In Site 2, only the available stem-bark area of 44,666 cm(2) was identified because no specimens were harvested. There is no difference in knowledge of this species regarding the gender and age. CONCLUSIONS: Stryphnodendron rotundifolium is a key resource for the studied community. A large proportion of bark collected from the first diameter size class may affect the growth of these individuals and may influence the recruitment process. Perhaps, this effect may explain the absence of individuals in some size classes.